Tar spot susceptibility of corn influences phyllosphere-associated bacterial and fungal microbiomes - Singh, Raksha; Sic-Hernandez, Wily R.; Crane, Charles F.; Shim, Sujoung; Telenko, Darcy E. P.; Goodwin, Stephen B. (Frontiers in Microbiology, 2025)
Tar spot, caused by the obligate fungal pathogen Phyllachora maydis, is a major economic concern for corn producers in the United States. To test the hypothesis that P. maydis can interact with other foliar microorganisms, we investigated phyllosphere microbiomes in relation to corn inbreds with differential tar spot symptoms under natural field infestation. Sixteen inbred lines were assessed for tar spot symptoms, and bacterial and fungal microbiomes were characterized using Illumina MiSeq Sequencing. Comparison of the phyllosphere microbiomes revealed distinct bacterial and fungal communities between resistant and susceptible lines in a sample-specific manner. Bacterial alpha diversity did not differ significantly between susceptible and resistant lines, while fungal diversity (richness, evenness, and phylogenetic diversity) was significantly higher in resistant lines. Beta diversity analysis revealed significant structural differences in both bacterial and fungal communities, with fungal differences more pronounced and driven by relative abundance. Resistant lines were associated with plant-beneficial bacterial genera such as Quadrisphaera, Klenkia and Nocardioides and fungal genera Cladosporium, Coniothyrium, Alternaria, Epicoccum, Bipolaris, Phyllozyma, and Papiliotrema, while susceptible lines were dominated by Erwiniaceae, Aureimonas, Pseudomonas, Microbacterium, and Deinococcus and fungal genera Hannaella, Paraphaeosphaeria, Sphaerellopsis and Phyllachora. Coniothyrium, a potential mycoparasite of P. maydis, was also detected but whether it is the same species that was identified in Central and South America is unknown. Our findings imply that P. maydis infection may result in a distinct, less diverse microbiome. Differential abundance analysis revealed enrichment of Erwiniaceae and Enterobacterales, particularly Amnibacterium in susceptible lines, and Microbacteriaceae in resistant lines. Correlation analysis between P. maydis reads and abundant taxa revealed a predominance of negative correlations, suggesting increased ecological niche differentiation driven by intense competition within the microbial community. These findings suggest that P. maydis infection is associated with a less diverse microbiome and that specific microbial taxa may play roles in P. maydis susceptibility and resistance. Further research on these correlated and distinct microbiotas could elucidate the role of foliar microbiomes in causing or resisting P. maydis infection.